Effectiveness and safety of direct oral anticoagulants in atrial fibrillation patients switched from vitamin K antagonists: A systematic review and meta‐analysis. Issue 1 (16th July 2019) - Hellfritzsch, Maja; Adelborg, Kasper; Damkier, Per; Paaske Johnsen, Søren; Hallas, Jesper; Pottegård, Anton; Grove, Erik Lerkevang
Abstract: A substantial proportion of atrial fibrillation patients initiating direct oral anticoagulants (DOAC) are vitamin K antagonists (VKA)‐experienced, for example switchers from VKA to DOAC. With this study, we aimed to summarize available evidence on the effectiveness and safety of DOAC vs VKA in real‐life VKA‐experienced atrial fibrillation patients. We searched EMBASE, MEDLINE and Cochrane Library systematically for English‐language studies indexed any time before October 2018. We included studies of VKA‐experienced atrial fibrillation patients initiating DOAC therapy, with continued VKA therapy as comparator. Outcomes included arterial thromboembolism and bleeding. When appropriate, meta‐analysis was performed by calculating pooled, weighted and adjusted hazard ratios (aHR) with 95% confidence intervals (CI). Eight cohort studies comparing VKA‐experienced DOAC (dabigatran or rivaroxaban) users with continued VKA users were included. When comparing DOAC to VKA, an increased risk of ischaemic stroke and myocardial infarction was found for dabigatran (pooled aHR of 1.61 [95% CI 1.19‐2.19, I 2 = 65%] and 1.29 [95% CI 1.10‐1.52, I 2 = 0%], respectively), but not for rivaroxaban. The use of dabigatran in VKA‐experienced users was associated with an increased risk of gastrointestinal bleeding (pooled aHR 1.63 [95% CI 1.36‐1.94, I 2 = 30%]), but a decreased risk of intracranial bleeding (pooled aHR 0.45 [95% CI 0.32‐0.64, I 2 = 0%]). In conclusion, the use of dabigatran in prior VKA users in clinical practice was associated with a slightly increased risk of arterial thromboembolism and gastrointestinal bleeding, but a decreased risk of intracranial bleeding. Importantly, observational studies of real‐life VKA‐experienced oral anticoagulant users may be confounded by the reason for switching.